2019
DOI: 10.5194/isprs-annals-iv-5-w2-111-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Urban Trees Within Cadastral Parcels Using an Object-Based Convolutional Neural Network

Abstract: Abstract. Urban trees offer significant benefits for improving the sustainability and liveability of cities, but its monitoring is a major challenge for urban planners. Remote-sensing based technologies can effectively detect, monitor and quantify urban tree coverage as an alternative to field-based measurements. Automatic extraction of urban land cover features with high accuracy is a challenging task and it demands artificial intelligence workflows for efficiency and thematic quality. In this context, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…Some parts of this section are repeated from an earlier paper by the two senior authors [57]. The CNN workflow of Trimble's eCognition software Developer 9.4 was applied for tree extraction ( Figure 7).…”
Section: Object-based Cnn For Tree Cover Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some parts of this section are repeated from an earlier paper by the two senior authors [57]. The CNN workflow of Trimble's eCognition software Developer 9.4 was applied for tree extraction ( Figure 7).…”
Section: Object-based Cnn For Tree Cover Identificationmentioning
confidence: 99%
“…The hidden units are like neurons that are fully connected with each individual neuron from a previous layer [49,51]. CNN has proven successful in vegetation contexts [52][53][54][55][56][57]. Li et al [52] used the CNN algorithm in very high-resolution quick bird images for oil palm trees detection in Malaysia and achieved 87.95% overall accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were three steps: (1) to generate sample patches of lodging and non-lodging classes, (2) to create and train the model, and (3) to test the model and report its performance [43,44]. Some studies have been reported that use the CNN algorithm in this software for trees identification and classification [45,46] and dwelling identification [47,48]. In this study, a customized architecture for the CNN was used, which included three hidden layers and one fully connected layer (Figure 2), and it was applied to the three models.…”
Section: Cnn Architecture and Experimental Designmentioning
confidence: 99%
“…CNN, a deep learning supervised neural network which uses labeled data, has been recognized as one of the most successful and widely used deep learning approaches [8,9]. For example, CNN has been used for object detection of trees [10][11][12][13][14][15], buildings extraction [16,17], ship detection [18,19], etc.…”
Section: Introductionmentioning
confidence: 99%